Noise extraction using frequency domain analysis - Riduan, Abdul Rahman (2012)
Noise is considered a hindrance in every vibrations signals including in an automotive suspension systems. Therefore methods of noise extraction were introduced in order to extract noise in the vibration signals. In this study noise are extracted from an automotive suspension system by frequency domain analysis. The vibrations frequency of the automotive spring is set to 8 Hz, 9 Hz and 10 Hz after that the automotive spring vibrations signals data were collected by using an accelerometer which connected to the suspension test rig which it functions were to measure the displacement of the spring, by using DASYLab® software. The vibrations signals it is then undergoes a low pass and high pass filter which is then interpreted in the form of power spectrum density which is done by fast-Fourier transforms which is then from the power spectrum density it is analyze to conduct noise extraction. The result is based on the ripple produce in power density spectrum of all the different frequency and also a different low-pass filter and high-pass filter. After that finding the most suitable frequency conditions for the low pass and high pass filter based on power spectrum density produce after filter process. The most optimum condition for noise extraction which achieved the most free noise vibration is when the low-pass filter is set to a frequency of 8 Hz and the high-pass filter is set to a frequency of 10 Hz.